Pengaruh Pemberian Ekstrak Okra (Abelmoschus Esculentus) terhadap Peningkatan Jumlah Eritrosit dan Kadar Hemoglobin (Hb) Darah Tikus Putih Jantan (Rattus Norvegicus) Anemia yang Diinduksi Natrium Nitrit (NaNO2) - Endah Setyarini; Enrico Kuswahyuliawan; Diah Hermayanti; Bragastio Sidharta (Puslitbang Sinergis Asa Professional, 2023)
Hemolytic anemia is a condition which the number of erythrocytes and hemoglobin levels are less than normal due to shortening of life span, rupture and destruction of erythrocytes. One of the factors causing the rupture and destruction of erythrocytes is oxidative stress. Okra contain flavonoid antioxidants that can counteract and prevent oxidative stress. This research to determine the effectiveness of okra (Abelmoschus Esculentus) extract on increasing the number of erythrocytes and hemoglobin (Hb) levels in the blood of anemia male white rats (Rattus Norvegicus) induced by sodium nitrite (NaNO2). Experiment with Posttest Only Control Group Design was held. The number of samples used were 24 male white rats (Rattus norvegicus) which were divided into 4 groups; the positive control group, which was only given NaNO2 and the other three groups were given NaNO2 and okra extract (Abelmoschus Esculentus) at 200mg/kgBW/day, 300mg/kgBW/day, and 400mg/kgBW/day for 28 days. Blood samples were taken and then the number of erythrocytes and hemoglobin levels were calculated using a hematoanalyzer. Anova test results obtained a significant value (sig, 0.000) between groups. Okra (Abelmoschus Esculentus) extract was able to increase the number of erythrocytes and hemoglobin (Hb) levels. Okra (Abelmoschus Esculentus) extract has an effect on increasing the number of erythrocytes and blood hemoglobin levels of anemic male white rats.